Origins of sediments and fluids in submarine mud volcanoes off Tanegashima Island, northern Ryukyu Trench, Japan - Ijiri, Akira; Setoguchi, Ryoma; Mitsutome, Yuki; Toki, Tomohiro; Murayama, Masafumi; Hagino, Kyoko; Hamada, Yohei; Yamagata, Takeyasu; Matsuzaki, Hiroyuki; Tanikawa, Wataru; Tadai, Osamu; Kitada, Kazuya; et al. (Frontiers in Earth Science, 2023)
Mud volcanoes are topographic features through which over-pressurized sediments are intruded upward and erupted. To understand material and biogeochemical cycling through mud volcanoes, we investigated the origins of sediments and fluids erupted by four submarine mud volcanoes off Tanegashima Island, along the northern Ryukyu Trench: MV#1-3 and MV#14. We estimated the ages of the source sequences of the mud volcano sediments to be middle to late Miocene based on nannofossils and 10 Be ages. The sediments were characteristically enriched in illite. The similar mineral compositions and vitrinite reflectance values (0.42%-0.45%) of sediments erupted by the mud volcanoes strongly suggest that each is rooted in the same source sequence. Porewaters had Cl − concentrations ~40% that of seawater and were proportionally enriched in 18 O and depleted in D, indicating the addition of freshwater from the dehydration of clay minerals. However, the smectite and illite contents (<40%) in the clay size fraction ruled out in situ smectite dewatering as the cause of the porewater Cl − dilution. Thus, fluids derived from clay dewatering must have originated from deeper than the source sequence of the mud volcano sediments. Vertical Cl − profiles indicate that the upward fluid advection rate and eruption frequency decrease from MV#3 to MV#2, MV#1, and MV#14 (MV#14 being dormant). At the active mud volcanoes, the C1/C2 ratios (<100) and methane δ 13 C values (−56‰ to −42‰) indicate that hydrocarbon gases are mostly derived from the thermal decomposition of organic matter in deep sediments where the in situ temperature exceeds 80 °C. At the dormant MV#14, high C1/C2 ratios (700-4,000) and low methane δ 13 C values (ca. −75‰) suggest the limited supply of thermogenic methane and the subsequent shallow methanogenesis. Because vitrinite reflectance values indicate that the source sediments are too immature to produce thermogenic hydrocarbons, the hydrocarbon gases, like the fluids derived from clay dewatering, were probably supplied from deeper than the source strata. The supply of deep fluids into the source sequence might be a universal phenomenon in subduction zones, and may play an important role in mud volcanism and associated biogeochemical cycling.